التعليم من أجل التنمية المستدامة: مقاربة أكاديمية - علي خالد عبد القادر (Tasnim International Journal for Human, Social and Legal Sciences, 2026)
This paper aims to highlight the pivotal role of education in achieving sustainable development, given the growing global concern for this pressing issue in contemporary times. Sustainable development revolves around three fundamental dimensions: the economic, social, and environmental aspects. To instill this concept in younger generations, it must be systematically integrated into educational curricula. Teaching and consolidating sustainable development requires the adoption of specific pedagogical methods, along with the provision of essential components related to both the learning process and the educational environment. Moreover, embedding sustainable development in education